A QUALITATIVE INVESTIGATION INTO MAJOR DETERMINANTS OF MARKET SELECTION BY A MULTINATIONAL INSURANCE COMPANY - Lee, Kyung Ho (2006)
By using a case study approach, this study reviews the internationalisation process of an American multinational insurance company and explores the major determinants of market selection for the entry into the German insurance market. Findings from the in-depth interviews suggest that American insurance companies take a simplistic approach towards internationalisation and base their market selection upon only a limited number of economic factors. Managers should use these results to reflect upon their market selection approach and critically question themselves about to what extent their decision is actually warranted by solid economic factors. In addition, the exploratory approach allowed the emergence of new factors that have not been explored before in relation to the insurance sector. The cultural receptivity to insurance products seems to be a major determinant of market selection. Finally, the results shed light upon the applicability of the existing internationalisation theory to the insurance sector